PERSPEKTIF HOLISTIK TARI MERADAI GARAPAN SEKOLAH MENENGAH KEJURUAN NEGERI 5 KOTA BENGKULU - Lara Sati, Ane Gempita; Maryono, Maryono (Institut Seni Indonesia Surakarta, 2023)
Bengkulu is one of the provinces located on the island of Sumatra with its capital city being Bengkulu City. Bengkulu City has a very famous ceremonial tradition, namely the Tabot ritual tradition which is held every year on the 1st to the 10th of Muharram. The Tabot ritual is often used as an entertainment event in the form of creative dance or new works created by local artists in Bengkulu City. One of them is the Meradai dance which is a work of State Vocational High School 5 of Bengkulu City in 2017. This study aims to reveal the meaning contained in the Meradai dance created by State Vocational High School 5 of Bengkulu City. The meaning of the dance is revealed by revealing three problems including: the genetic concept, the form of purpose, and the audience's response to the Meradai dance created by State Vocational High School 5 of Bengkulu City. This study uses a holistic art criticism approach that places three factors, namely genetic, objective, and affective, which are a unity as a source of the flow of meaning. This study is qualitative with data collection techniques including interviews, observations, and literature studies. The results of the discussion based on genetic factors, objectives, and affective aspects of the Meradai dance created by State Vocational High School 5, Bengkulu City are used for competitions, entertainment and learning materials, and contain values ​​of fighting spirit, mutual cooperation, and cultural history values.